Fabrication of high mechanical performance UHMWPE nanocomposites with high‐loading multiwalled carbon nanotubes. Issue 19 (12th November 2019) - Wang, Rui; Zheng, Yanyu; Chen, Lihao; Chen, Shaoyun; Zhuo, Dongxian; Wu, Lixin
ABSTRACT: Using conventional mixing techniques, the mechanical properties of prepared carbon nanotube (CNT)/polymer composites are not impressive enough, because of their aggregation problem at a high loading of CNTs. In this article, high mechanical performance ultrahigh molecular weight polyethylene (UHMWPE) nanocomposites with high loading of multiwalled CNTs were successfully fabricated by a new manufacturing technique. Specifically, the tensile strength and storage modulus at 25 °C of UHMWPE nanocomposites with 32 wt % of nanotubes prepared by the novel technique reaches 107.6 MPa and 6.0 GPa, respectively, about 4.7 times and 5.0 times of that of pure UHMWPE resin, which are also very high experimental results compared with polyethylene nanocomposite prepared by traditional hot‐compression techniques. These attractive results suggest that the high‐loading CNTs without sacrificing their dispersion and the impregnation quality of polymer‐impregnated buckypapers are essential for fabricating CNTs/polymer composites with superior mechanical properties. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48667. Abstract :